The effectiveness of traditional Basic Life Support training and alternative technology-enhanced methods in high schools. Issue 1 (January 2019) - Onan, Arif; Turan, Sevgi; Elcin, Melih; Erbil, Bulent; Bulut, Şule Çınar
Background: Implementation of resuscitation training in school programs is a promising approach to improve rates of cardiopulmonary resuscitation use by trained bystanders. Unfortunately, theoretical cardiopulmonary resuscitation instruction alone is not sufficiently effective in developing practical skills. Objectives: This study aimed to investigate the effectiveness of traditional Basic Life Support training and alternative instructional methods to achieve learning objectives of Basic Life Support education. Methods: This quasi-experimental study was conducted in a secondary school in Ankara, Turkey. Eighty-three voluntary students were randomly allocated to theoretical (Group A), video-based (Group B), and mobile-assisted video-based instructions (Group C). All groups were led by the course teacher. Assessments were conducted in training and again 1 week later. Assessments were based on Basic Life Support knowledge and confidence performance scores. Results: Statistically significant difference was found for the groups' Confidence Scale scores (F(2, 73) = 3.513, p = 0.035, ηp 2 = 0.088); Group C (6.76 ± 1.70) scored higher than Group A. The groups' Basic Life Support checklist scores were statistically significant (F(2, 73) = 28.050, p = 0.000, ηp 2 = 0.435); Group C (32.32 ± 3.84) scored higher than the other groups. Statistically significant difference was found for the groups' measurable Basic Life Support scores (F(2, 73) = 13.527, p = 0.000, ηp 2 = 0.270); and Group C (23.76 ± 3.98) scored higher than the other groups. Conclusion: Our findings showed that all instruction methods led to increased Basic Life Support knowledge scores. The mobile-assisted program significantly increased knowledge scores. Same-group high-quality cardiopulmonary resuscitation parameters were more positive than the other instruction groups except for hand position. Group C students expressed higher confidence in their ability to act in an emergency when witnessing a victim collapse.